Analisis Kesalahan Bidang Morfologi pada Karangan Deskriptif Siswa Kelas X-1 SMA Negeri I Cepogo Boyolali dan Implementasinya Sebagai Bahan Ajar - Maesaroh, Siti (2016)
Siti Maesaroh. S200140044. Analysing The Morphology' Error At Descriptive Writing Text By Students of SMA Negeri I Cepogo Boyolali and Implemented As Teaching Media. Surakarta. Graduate Program of Indonesian Education Muhammadiyah University, 2015. Three objectives of this research. 1) To describe the morphology's error made by Class X-1 SMA Negeri 1 Cepogo when written descriptive text. 2) To explain why Class X-1 of SMA Negeri 1 Cepogo made at morphology's error. 3) The students writings product is implemented as teaching media. This research is related to descritive qualitative using tunggal terpancang strategy. The subject of the research are students of class X-1 and Indonesian teachers but the objects of the research is the students' product of writing descriptive text made by students of class X-1 SMA Negeri 1 Cepogo . In collecting the data, the researcher uses, interviews, and writes. The researcher uses padan and agih to analyse the data by inductive analyst. The analysing product shows there are 1) 203 errors at morphology subjects of descriptive text made by students of SMA Negeri 1 Cepogo. Most of the them are classified into seven characters is affixture 18,72 %, reduplication 15,27%, preposition 23,15%, diction 21,68%, the fault of contamination 0,98%, composition 2,96% and pleonastic 17,24%. 2) It is indicated that most of the students error above are caused by the students and teachers. 3) The results of the analysis can be implemented as Indonesian teaching materials in SMA because studenst can avoid the morphology's error in writing a descriptive text. It is proven on the basis of competence 4.2 which is writing the results of observations in the form of a descriptive text using linguistic rules of the correct morphology field